Digital Competence and Professional Development on Action Research Capability of Basic Education Teachers - Servancia III, Bonifacio Roger; Escarlos, Gladys (Journal of Interdisciplinary Perspectives, 2025)
This study examined the influence of digital competence and professional development on the action research capability of basic education teachers in Maramag 1 District, Bukidnon. Using descriptive statistics and correlation coefficients, the research identified predictor variables affecting teachers' action research capabilities. Teachers demonstrated a high level of digital competence across various domains, including technological operations, social and ethical, pedagogical, and professional. They also demonstrated high levels of professional development through training and seminars attended, as well as self-efficacy and advanced degrees. However, their action research capabilities were rated as moderately capable, particularly in areas such as topic selection and data analysis. The study found significant relationships between digital competence, professional development, and action research capability. This indicates that increasing digital competence and professional development significantly enhances teachers' action research capabilities, leading to the rejection of the null hypothesis, which states that there is no relationship between digital competence and professional development on the action research capability of basic education teachers.